DAYA TERIMA DAN KARAKTERISTIK MINUMAN SERBUK ‘TERAI’ BERBAHAN DASAR TEMULAWAK (Curcuma xanthorriza Roxb) DAN SERAI (Cymbopogon Citratus) - Yola Mastika Sari; Ayu Pravita Sari; Miratul Haya (Jurnal Vokasi Keperawatan (JVK), 2021)
Background : Powder drink is a powder or granule product that made from a mixture of sugar and spices with or without the addition of other ingredients. Raw ingredients of powder drink can make from various kinds of plants, such as turmeric and lemongrass, that are both of ingredients contain active compounds that can function to maintain body immunity, especially during a pandemic like now. The criterias of a good powder drink are taste, smell, color and appearance that are comparable to fresh products, have nutritional characteristics and have a good storage stability.Purpose : This study aims to determine the organoleptic acceptability of the "Terai" powder drink with three treatments and characteristics with the parameters of the water content and ash content of the most liked product.Methods : This research is an experimental research or experiment (experiment research). The design used is a completely randomized design which aims to assess a treatment or action. In this study, the treatment is carried out to determine the acceptability of "Terai" powder drink based on organoleptic colour, texture, aroma, and taste carried out on 30 trained panelists as well as characteristic tests with parameters of water content and ash content of the most liked product. The tests used are Kruskall-Wallis and Mann-Whiteney..Results : The result test of three product (F1, F2, F3) showed there was a difference of color receivability organoleptic (p=0,000) and taste (p=0,004), and smell receivability organoleptic (p=0,273) and texture (p=0,288) shwed there was no difference. So for receivability orgaanoleptic of colour and taste to be continued with Mann-Whitney test. . The result of the characteristic test with the water content parameter was 7.22% and the characteristic test result with the ash content parameter was 2.11% for the most preferred product.Conclusion : From three of ‘Terai’ powder drink’s  formulation showed that the most liked product is F2 with the water content 7,22% and the ash contenct 2,11%.